THE EFFECT OF INTERNSHIP EXPERIENCE, SELF-EFFICACY AND SOFT SKILLS ON JOB READINESS GENERATION Z IN JABODETABEK - Herawati, Herawati; Turangan, Joyce A. (International Journal of Application on Economics and Business, 2025)
Generation Z, as the age group with the highest unemployment rate, faces challenges in meeting the required job qualifications. This study aims to analyze the influence of internship experience, self-efficacy, and soft skills on job readiness in Jabodetabek. The study uses a descriptive method with a sample of 150 respondents selected through non-probability sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that internship experience, self-efficacy, and soft skills have a positive and significant impact on job readiness. This research was conducted due to the observation that many Generation Z graduates or students are still unprepared to enter the workforce, indicated by a lack of basic professional competence and soft skills. This study provides new insights for companies and readers regarding the importance of these factors in improving Generation Z's job readiness and reducing the unemployment rate among them.